(untitled) (Research, Society and Development, 2021)
Introduction: Monostotic fibrous dysplasia involving the maxillofacial region is more frequent in the maxilla and may occur in other bones. In most cases, the condition is asymptomatic and has a slow growth, with self-limited evolution, associated with skeletal maturation. Conservative surgical treatment is the preferred approach, whenever possible. Objective and case report: The article aims to present the report of a clinical case of a young patient diagnosed with zygomatic-maxillary monostotic fibrous dysplasia. The proposed treatment was the resection of the lesion and immediate reconstruction of the defect with a lyophilized bovine bone graft. The graft was maintained with a titanium microplate and screws. The patient remained under clinical and imaging control with no evidence of recurrence in the six-year postoperative follow-up. Final considerations: In the immediate reconstruction, the lyophilized bovine bone graft acted as an osteoconductive framework and favored the volumetric recovery of the area providing support for the reorganization of the bone defect.